2018
DOI: 10.1155/2018/9150723
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Differentially Expressed Genes in Porcine Ovaries at Proestrus and Estrus Stages Using RNA-Seq Technique

Abstract: Estrus is an important factor for the fecundity of sows, and it is involved in ovulation and hormone secretion in ovaries. To better understand the molecular mechanisms of porcine estrus, the expression patterns of ovarian mRNA at proestrus and estrus stages were analyzed using RNA sequencing technology. A total of 2,167 differentially expressed genes (DEGs) were identified (P ≤ 0.05, |log2  Ratio| ≥ 1), of which 784 were upregulated and 1,383 were downregulated in the estrus compared with the proestrus group.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 54 publications
0
18
0
Order By: Relevance
“…different patterns of gene expression [48]. In this study, there were polymorphisms of gene expression clusters between O. mekongensis and O. songkhramensis.…”
Section: Plos Onementioning
confidence: 55%
See 1 more Smart Citation
“…different patterns of gene expression [48]. In this study, there were polymorphisms of gene expression clusters between O. mekongensis and O. songkhramensis.…”
Section: Plos Onementioning
confidence: 55%
“…songkhramensis , as annotated by KOG, GO and KEGG. Regarding TF expression and DEGs, TFs have been investigated as an important step in gene regulatory networks [ 47 ], and DEGs are utilized as potential markers to observe different patterns of gene expression [ 48 ]. In this study, there were polymorphisms of gene expression clusters between O .…”
Section: Discussionmentioning
confidence: 99%
“…Yang et al compared the gene expression profiles of the proestrus and estrus stages. The authors identified more down-regulated genes in the estrus group when compared to the proestrus group, and demonstrated that the sow estrous cycle affects sow fecundity [31]. These two studies indicate that several genes could affect estrus.…”
Section: Discussionmentioning
confidence: 91%
“…A previous study of the ovary screened the major functional genes or molecular markers of estrus expression during diestrus and estrus in gilts from two different breeds [6]. In addition, previous research has provided comprehensive transcriptome data on the porcine ovary at the proestrus and estrus stages through RNA-seq technology [7]. Although we previously analyzed the whole estrous cycle using RNA-seq, we focused on the interaction and connectivity between three reproductive tissues (ovary, oviduct, and endometrium), rather than on examining the changes that occurred during the estrous cycle in a particular tissue [8].…”
Section: Introductionmentioning
confidence: 99%